PENGARUH KEMAMPUAN BAHASA INGGRIS TERHADAP PRESTASI TARUNA TINGKAT IV AKADEMI MILITER - Agustin Nurhandayanti; Aris Basuki; Frangky Silitonga (JURNAL MAHATVAVIRYA, 2022)
One of the most important components in communication is language, the international language that has been used so far is English. The role of the TNI AD also has an impact on an international scale, so a soldier is considered more capable when he can master international languages. The educational institution for Indonesian Army soldiers is the Military Academy which is responsible for the English language skills of cadets' achievements. The research method used is a quantitative method. The data source sample is 68 cadets from a population of 216 cadets. The data collection technique used a questionnaire that measured the level of cadets' English skills and was associated with the cadets' achievement scores. these results are the result of learning and experiences of visits abroad. The problem is the achievement and ability of the cadets' English language skills, as well as the influence of English language skills on the achievement of level IV cadets. The results of the correlation test, there is no relationship between mastery of English and the achievement of level IV cadets in the Akmil. The significant value is 0.566, it can simply be explained based on the limit of the significance value used is 0.05 where the test results are > of the significance value. However, with good or sufficient English skills, they have the opportunity to develop their experience around 83.3% are selected abroad.